Comparing open and closed vertical refrigerated display cabinets at mild and tropical external environments - Heidinger, Gustavo Galdi (2019)
This paper reports the results of experimental tests performed according to ISO 23953 in vertical open and closed refrigerated display cabinets (VORDC vs. VCRDC). Tests were performed at a mild climate class (n. º 3: T=25°C; φ=60%) and a tropical one (n. º 6: T=27°C; φ=70%). The direct energy consumption is 46% higher at VCRDC due to the heated glass doors frame and defrost heaters. The product simulator temperature is higher and more stable at VORDC. The highest product simulator temperature is lower (-1.4°C) at the VCRDC and less stable (+2.7°C variation) due to the opening doors period. The total mass of condensed water at the evaporator is reduced 87% and the total heat load is 77% lower at the VCRDC. Thus, the estimated total energy consumption is reduced 42%. Given the current concerns with energy consumption and sustainability of the heat exchange processes, the VCRDC provide the best solution.